Front Cover. (3rd March 2020) - Gould, John; Clulow, John; Clulow, Simon
Abstract : Lechriodus fletcheri tadpoles feeding around the perimeter of a recently laid conspecific spawn body. Photograph reproduced with the permission of John Gould, based on the Behavioural Note, Food, not friend: Tadpoles of the sandpaper frog (Lechriodus fletcheri) cannibalise conspecific eggs as a food resource in ephemeral pools by J. Gould, J. Clulow & S. Clulow, https://doi.org/10.1111/eth.12995